Teachers’ and Principals’ Perception to Total Quality Management Practices in Lagos State Secondary Schools - Ogunwale, Ogundiran Samuel (NIU Journal of Humanities; Vol 3 No 4 (2018): KIU Journal of Humanities, Vol. 3 No. 4, December 2018, 2019)
This study ascertained the total quality management practices in Agege Local Government Area secondary schools in Lagos state. The research design adopted was a descriptive survey. Ten principals, 20 vice-principals and 100 teachers were selected through random sampling technique. The instrument for data collection was a researcher's self-designed questionnaire titled "Total Quality Management Assessment Questionnaire (TQMAQ). Three research questions guided the study. Data collected were analyzed with descriptive statistics, precisely mean and standard deviation. Findings of the study revealed that effective communication and follow-up of the educational process were practiced to a very high extent. Findings also revealed that the principle of total commitment is being practiced to a low extent in secondary schools in Agege Local Government Area of Lagos state. Based on the findings, the researcher recommended that government agencies such as Education District Areas and Ministry of Education should try to maintain standards by carrying out periodic inspection of staff recruited and whether they are abreast with the current challenges of the 21 st century classroom management, and principals should be fully committed to TQM application for effective school administration. Keywords: Assessment, total, quality management, secondary schools.